Immunopathology of lung transplantation: from infection to rejection and vice versa - Righi, Ilaria; Barone, Ivan; Rosso, Lorenzo; Morlacchi, Letizia Corinna; Rossetti, Valeria; Caffarena, Giovanni; Limanaqi, Fiona; Palleschi, Alessandro; Clerici, Mario; Trabattoni, Daria (Frontiers in Immunology, 2024)
Lung transplantation offers a lifesaving option for patients with end-stage lung disease, but it is marred by a high risk of post-transplant infections, particularly involving multidrug-resistant bacteria, Cytomegalovirus, and fungal pathogens. This elevated infection rate, the highest among solid organ transplants, poses a significant challenge for clinicians, particularly within the first year post-transplantation, where infections are the leading cause of mortality. The direct exposure of lung allografts to the external environment exacerbates this vulnerability leading to constant immune stimulation and consequently to an elevated risk of triggering alloimmune responses to the lung allograft. The necessity of prolonged immunosuppression to prevent allograft rejection further complicates patient management by increasing susceptibility to infections and neoplasms, and complicating the differentiation between rejection and infection, which require diametrically opposed management strategies. This review explores the intricate balance between preventing allograft rejection and managing the heightened infection risk in lung transplant recipients.